Orbital Angular Momentum Anti-interference Properties Analysis of Electromagnetic Vortex Wave - Yifeng LIN; Mingming SHAN; Xudong KONG; Qiang FENG; Long LI (Leida xuebao, 2021)
The electromagnetic vortex wave has demonstrated excellent research value with potential applications in the fields of wireless communication and radar detection and imaging due to its unusual electromagnetic field distribution and theoretically infinite orthogonal Orbital Angular Momentum (OAM) modes. This study analyzes the anti-interference performance of OAM modes in the electromagnetic vortex Radio Frequency (RF) transceiver link primarily from the perspective of the electromagnetic vortex field distributions in space and the OAM modes orthogonality. Planar antenna arrays are designed to generate the electromagnetic vortex beams with respective OAM modes of and in the C band, and the corresponding RF transceiver links are established. The OAM modes’ anti-interference properties under different interference situations are analyzed in the electromagnetic vortex RF transceiver link by using a horn antenna as the interference source. Meanwhile, the corresponding OAM mode spectrum and the OAM modes’ orthogonality are employed as the primary methods in our analysis. Finally, the designed antenna models are fabricated, and the electromagnetic vortex RF transceiver links are measured. The corresponding analyses and conclusions are presented in this study. The OAM modes’ anti-interference performance analysis in the vortex electromagnetic wave’s RF transceiver link can provide a reference for exploring and designing a vortex electromagnetic wave in wireless communication and radar detection and imaging research.